Sustainable Investment Practices: Bibliometric Analysis on Ten Years of Observations in ESG Agencies - A, García G. Sorely; F, Montes G. Luis; H, Romero, Carmen; M, Gutiérrez L., José; César, Zapata-Molina; A, Romero, Pedro; Mariana, Bravo-Sepúlveda; Harley, Guerrero-Latorre, Jorge (International Journal of Membrane Science and Technology, 2023)
Objective: To analyze sustainable investments by means of a bibliometric study using the SLR technique applied to scientific research records on ESG agencies, and the indices used, over a ten-year period from 2013 to 2023. Methodology: It is a qualitative and documentary research that relies on hermeneutics for the interpretation of written texts. In addition, a bibliometric analysis was made by means of a systematic and structured review of the literature following the SLR method, applied to the scientific records of the Scopus database. Results: This study found that companies’ intangible assets should be represented by stock market indices that show a responsible commitment to the environment. Therefore, governance plans should address more convincingly the priorities of socially responsible investment. Conclusions: A standardization of institutional ESG indicators is required to make the results of the measurements made on companies worldwide to demonstrate corporate sustainability more understandable and transparent and disclosed to the public. Originality: This research provides current knowledge on the factors used by ESG agencies to measure the sustainability of companies worldwide. The business world needs to be informed of these research advances, because there is a great diversity of aspects that must be considered for companies to achieve the sustainability they deserve, and a standard that facilitates a better measurement of sustainable investment indexes has not yet been established.